Mixed Micellization Behavior of (Chlorpromazine Hydrochloride + Cetyltrimethylammonium Bromide) System in Aqueous Solutions of Glycine. Issue 2 (2nd February 2021) - Banipal, Parampaul K.; Sharma, Jyoti; Sohal, Pallavi; Banipal, Tarlok S.
Abstract: We have examined the mixed micellar behavior of {amphiphilic drug; chlorpromazine hydrochloride (CPZ) + cationic surfactant; cetyltrimethylammonium bromide (CTAB)} at varying mole fractions of CPZ ( α CPZ = 0.2, 0.4, 0.6, and 0.8) in (0.1, 0.3, and 0.5) mol kg −1 glycine(aq) solutions at 298.15, 308.15, and 318.15 K, by using conductometric, volumetric, isentropic compressibility, UV–visible absorbance, fluorescence, and dynamic light scattering (DLS) techniques. The critical micelle concentration ( CMC ) values obtained from above measurements have been utilized to calculate the thermodynamic parameters (Δ G ° m, Δ H ° m, and Δ S ° m ) and degree of ionization ( α ) at studied temperatures and concentrations. The partial specific volume ( φ v ), partial specific isentropic compression ( φ κ ), and isentropic compressibility ( κ s ) have been calculated from the experimental density and speed of sound measurements and the results have been used to elucidate different interactions occurring in these systems. These results are further supported by UV–visible absorbance and fluorescence spectroscopic studies. The hydrodynamic diameters ( D h ) of the mixed micellar system have been measured from the DLS studies. Thermodynamic and spectroscopic studies depict the dominance of hydrophobic/hydrophilic‐hydrophobic interactions between the alkyl (R = C16 H33 ) chain of CTAB or hydrophobic tricyclic scaffolding of CPZ/Br − /N + ‐CH3 group of CTAB or hydrophilic group i.e ., tertiary amine portion of CPZ with hydrophobic group of glycine. Abstract :